(untitled) (Revista de História da UEG (REVHIST), 2024)
This article aims to develop a study about the appropriation of the classical political concept imperium by the Florentine poet Dante Alighieri in his political treaty De Monarchia. Terms and concepts are constantly changing over time and receive singular appropriations, depending on their historical use. Dante incorporates the term imperium in his studies, as was common in the reality of medieval thinkers. In De Monarchia, the concept plays a central role in his political and historical perspective on how to solve the problems of the Italic peninsula. Through his notion of empire and the use of the history of the Roman people, this study aims emphasize the uniqueness of political thought on Dante as a possibility to understand the events and the forms of political and history produced in Late Middle Ages. Key Words: Politics. Medieval. History. Rome. Imperium.